Mycoheterotrophy in the wood-wide web - Merckx,VSFT; Gomes,SIF; Wang,D; Verbeek,C; Jacquemyn,H; Zahn,FE; Gebauer,G; Bidartondo,MI (Nature Plants, 2024)
The prevalence and potential functions of common mycorrhizal networks, or the 'wood-wide web', resulting from the simultaneous interaction of mycorrhizal fungi and roots of different neighbouring plants have been increasingly capturing the interest of science and society, sometimes leading to hyperbole and misinterpretation. Several recent reviews conclude that popular claims regarding the widespread nature of these networks in forests and their role in the transfer of resources and information between plants lack evidence. Here we argue that mycoheterotrophic plants associated with ectomycorrhizal or arbuscular mycorrhizal fungi require resource transfer through common mycorrhizal networks and thus are natural evidence for the occurrence and function of these networks, offering a largely overlooked window into this methodologically challenging underground phenomenon. The wide evolutionary and geographic distribution of mycoheterotrophs and their interactions with a broad phylogenetic range of mycorrhizal fungi indicate that common mycorrhizal networks are prevalent, particularly in forests, and result in net carbon transfer among diverse plants through shared mycorrhizal fungi. On the basis of the available scientific evidence, we propose a continuum of carbon transfer options within common mycorrhizal networks, and we discuss how knowledge on the biology of mycoheterotrophic plants can be instrumental for the study of mycorrhizal-mediated transfers between plants.